Tomato responses to salinity stress: From morphological traits to genetic changes - Roșca, Mihaela; Mihalache, Gabriela; Stoleru, Vasile (Frontiers in Plant Science, 2023)
Tomato is an essential annual crop providing human food worldwide. It is estimated that by the year 2050 more than 50% of the arable land will become saline and, in this respect, in recent years researchers have focused their attention on studying how tomato plants behave under various saline conditions. Plenty of research papers is available regarding the effects of salinity on tomato plant growth and development, that provides information on the behavior of different cultivars under various salt concentrations, or experimental protocols analyzing various parameters. This review gives a synthetic insight of the recent scientific advances relevant to the effects of salinity on the morphological, physiological, biochemical, yield, fruit quality parameters and on the gene expression of tomato plants. Notably, the works that assessed the salinity effects on tomatoes were firstly identified in Scopus, PubMed and Web of Science databases, followed by their sifter according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline and with an emphasis on their results. The assessment of the selected studies pointed out that salinity is one of the factors significantly affecting tomato growth in all stages of plant development. Therefore, more research to find solutions to increase the tolerance of tomato plants to salinity stress are needed. Furthermore, the findings reported in this review are helpful to select and apply appropriate cropping practices to sustain tomato market demand in a scenario of increasing salinity in arable lands due to soil water deficit, use of low-quality water in farming and intensive agronomic practices.